Manganese Superoxide Dismutase Expression Regulates the Switch Between an Epithelial and a Mesenchymal-Like Phenotype in Breast Carcinoma - Loo, Ser Yue (MARY ANN LIEBERT, INC, 2023)
10.1089/ars.2015.6524